Point mutation in the S gene of hepatitis B virus for a d/y or w/r subtypic change in two blood donors carrying a surface antigen of compound subtype adyr or adwr. - Okamoto, H (1987)
Genomes of hepatitis B virus (HBV) were cloned from the plasma of a blood donor who carried subviral particles of three distinct subtypes in the following proportions: adr, 25%; ayr, 63%; and adyr, 12%. HBV DNA clones were classified into two groups based on a difference at only one nucleotide in the S gene. Two clones had A as nucleotide 365 that formed part of the codon for lysine as amino acid residue 122 and produced a surface antigen of subtype adr in transfected NIH 3T3 cells. The remaining four clones had G determining the codon for arginine and produced a surface antigen of subtype ayr in transfected cells. Similarly, HBV genomes were cloned from the plasma of an individual who carried subviral particles of subtypes adr (71%) and adwr (29%). Two clones had T and A as nucleotides 476 and 479, respectively. The other seven clones had C and G as the respective nucleotides. Based on a comparison with previously reported HBV genomes of various subtypes, the mutation of nucleotide 479, forming part of the codon for lysine or arginine as amino acid residue 160, was deduced to determine the w or r subtype, respectively. When NIH 3T3 cells were transfected separately with the genome of subtype adw or adr, derived from plasma containing a surface antigen of subtype adwr, and then cocultured, they produced subviral particles of either subtype adw or adr. When cells were transfected with the genomes of subtypes adw and adr simultaneously, however, subviral particles were produced that possessed w and r determinants on the selfsame particles. These results attributed the d/y or w/r subtypic change to a point mutation in the S gene and favored coinfection of hepatocytes with an HBV genome and its mutant as the mechanism of compound subtypes.